High-speed centrifugation reduces immune rejection by removing bone marrow elements from fresh osteochondral allografts - Yongsheng Ma; Wenming Yang; Qitai Lin; Meiming Li; Zehao Li; Yugang Xing; Lei Wei; Wangping Duan; Xiaochun Wei (Journal of Orthopaedic Translation)
Background: Fresh osteochondral allografts (OCAs) contain numerous immunogenic components in the subchondral bone (SB). Whether high-speed centrifugation (HSC) reduces immune rejection by removing bone marrow elements (BMEs), compared to methods without HSC, remains unknown. This study aimed to validate the efficacy and safety of HSC in reducing immune rejection by removing allogeneic BMEs. Methods: OCAs were obtained from the femoral condyles of the stifle joint in 18 pigs. Gross observations, histological staining, weight measurements, and DNA extraction were performed to assess the effects of centrifugation speed and duration on BMEs removal in OCAs. The effect of HSC on OCAs preservation was determined in vitro using microbiological testing, live/dead cell staining, and histological staining. Moreover, the co-culture effect of RAW264.7 cells and OCAs with or without HSC in vitro was evaluated using enzyme-linked immunosorbent assay (ELISA), histological staining, and immunohistochemical staining. The transplantation effect of OCAs with or without HSC was examined in vivo using a subcutaneous mouse model. Finally, the residues in the centrifuge tubes were analysed using ELISA, haematoxylin and eosin (HE) staining, and metabolomic analysis. Results: Centrifugal speeds of 12000 rpm for 1 min were sufficient to reduce BMEs by over 90 %. HSC had a protective effect on chondrocytes and the extracellular matrix during the in vitro preservation of OCAs. In addition, OCAs using the HSC method exhibited reduced recognition by the host immune system compared with OCAs without HSC, thereby reducing immune rejection. Lipids were the most abundant and difficult-to-remove antigenic components and are the most likely to affect host macrophage polarisation, playing an important role in immune rejection. Conclusion: Our study demonstrated that HSC method significantly reduces immune rejection by removing BMEs from OCAs. The translational potential of this article: Our study demonstrated that HSC is a simple, efficient, and safe physical method for removing antigenic components from OCAs, effectively reducing immune rejection and highlighting its clinical potential.